Factors influencing the utilization of learning management system among aviation academy students - AlShaikhi, Mohammed Ahmed Ali (2019)
Recently, in the context of higher education, the use of Learning Management System (LMS) involving the application of Information Communication Technologies (ICT) has become Widespread. The LMS is actually a software based computer program that enables to design, manage and change different learning courses as student can learn quickly and effectively. Despite the advantages of LMS in enhancing the quality of learning, it is not fully utilized by Saudi students. Review of the related studies shows that although there is an enormous amount of research an online tools, only a few of them have investigated how Saudi students use the online tools found within LMS. The main purpose of the present study is to investigate the influence of external factors and mediators on Learning Management System utilization among the Saudi Academy of Civil Aviation (SACA) based on Unified Theory of Acceptance and Use of Technology (UTAUT) and Motivation Model Attention, Relevance, Confidence, and Satisfaction (ARCS). By reviewing the related literature, the influence of six factors on LMS utilization (performance expectancy, effort expectancy, social influence, facilitating conditions, motivation and behavioural intention to use) were examined. The present study was entirely quantitative with a descriptive design. The main instrument used was a questionnaire whose content validity was checked by a panel of experts. A pilot study was conducted on 30 students of SACA to assess the reliability of the instruments. The value of Cronbach’s alpha was from 0.81 to 0.93. The sampling technique was proportional stratified random sampling and the sample size was 167 SACA students. To analyse the data, descriptive statistics and the Structural Equation Modeling Technique were used.The finding of this study indicated that there was a high level of utilization of LMS (m = 3.54 with SD = 0.95) among the SACA students. The factors performance expectancy (m = 3.52 with SD = 0.60), effort expectancy (m = 3.49 with SD = 0.92), social influence (m=3.18 with SD=0.93), facilitating conditions (m = 3.36 with SD = 0.77), motivation (m=3.61 with SD= 0.94) and behavioural intention (m = 3.62 with SD = 1.04) were found to be high, whereas social influence was at moderate level (m = 3.18 with SD = 0.93). The results indicated that the motivation was shown to be the most salient factor influencing the use of LMS (β = .0375, p = .001), followed by facilitating conditions (β =.374, p = .027), effort expectancy (β = .321, p = .032) and social influence (β = .268, p = .044), while performance expectancy has not had any significant influence on LMS usage (β=.021; p =.752). Finally, the influence of motivation, facilitating conditions, effort expectancy and social influence on the use of LMS were found to be mediated by behavioural intention. The study proposes a model which can be utilized as a guide to facilitate future researches in related areas.